(3GdaUhds - (3CMeO Hf hUhd, CHh LYaQs
(3ChdgG (B:s
(3bGd CMeO Hf hUhd (B: (3CMSf eG GSJaJM Hg Gdbhd hbOe Hjf jOi GdYed MeO Gddg GdCYR hGdCLd s
(3BNQgG (B:s
(3hcd eeG QH aGdEeGe ajg eNjQ , eGde jbJd aEf bJd de jcf ddEeGe ajg NjGQ , hhLH Ydjg bJdg GfJgi cJGH GdaUhd dCMeO Hf hUhd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdabg GdeGdcjs